2016
DOI: 10.1007/s00268-016-3530-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation in Trauma Patients: The First 24 h is Different!

Abstract: The acute phase is different from the subsequent phase of care and there appears to be some inappropriate extrapolation of ICU practice to the acute phase. Application of the proposed ventilation strategies should ensure an optimal outcome. It is important to treat patients as individuals during assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…It is unfortunate that—due to the different pathophysiological mechanisms of ALI and safety issues—most important trials of lung protective ventilation exclude patients with ABI. Nevertheless, some studies have reported that ventilation with low VT achieves better neurophysiological protection and that this is associated with a lower incidence of ALI in critically ill neurological patients [ 13 , 95 , 96 ], although it still debated whether the protective ventilation strategy should be extrapolated to the prehospital and emergency environment during the acute resuscitative phase (12–24 h) [ 97 ]. Despite the lack of robust evidence, the recent recommendations of the European Society of ICM state that there is a consensus that the optimal range of PaCO 2 lies between 35–45 mmHg [ 91 ].…”
Section: Ventilatory Strategies In Acute Brain Injury: What Is Different?mentioning
confidence: 99%
“…It is unfortunate that—due to the different pathophysiological mechanisms of ALI and safety issues—most important trials of lung protective ventilation exclude patients with ABI. Nevertheless, some studies have reported that ventilation with low VT achieves better neurophysiological protection and that this is associated with a lower incidence of ALI in critically ill neurological patients [ 13 , 95 , 96 ], although it still debated whether the protective ventilation strategy should be extrapolated to the prehospital and emergency environment during the acute resuscitative phase (12–24 h) [ 97 ]. Despite the lack of robust evidence, the recent recommendations of the European Society of ICM state that there is a consensus that the optimal range of PaCO 2 lies between 35–45 mmHg [ 91 ].…”
Section: Ventilatory Strategies In Acute Brain Injury: What Is Different?mentioning
confidence: 99%
“…Deviations in PaCO 2 values are tolerated in some trauma scenarios (mainly as part of lung-protective ventilation strategies), but PaCO 2 abnormalities have been shown to impose a major risk to an injured brain, and thus should be avoided in the acute phase following TBI [ 16 , 45 , 46 ]. These alterations can result either from trauma, or they can be iatrogenic in intubated and mechanically ventilated patients.…”
Section: Perioperative Cardiorespiratory Optimizationmentioning
confidence: 99%
“…Utilization of simultaneous multisystem surgery (SMS) is gradually becoming recognized as a useful tool in this context [ 12 , 13 , 14 ]. Some of the treatments utilized to manage polytrauma patients without TBI, including those of the damage control surgery (DCS) and the damage control resuscitation (DCR), are contraindicated when TBI is present, and can impose an additional risk to a patient’s survival and functional outcome [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ventilatory strategies in trauma patients could take into account the phase of treatment and the underlying injuries [45].…”
Section: Rescue Strategies For Refractory Respiratory Failurementioning
confidence: 99%